Biopsychosocial Attributes of Single-region and Multi-region Body Pain During Early Adolescence: Analysis of the ABCD Cohort. Issue 11 (12th November 2022) - Senger-Carpenter, Thea; Scott, Eric L.; Marriott, Deanna J.; Lenko, Rachel; Seng, Julia; Ploutz-Snyder, Robert; Robinson-Lane, Sheria G.; Cofield, Cherie; Chen, Bingxin; Voepel-Lewis, Terri
Abstract : Objectives: Multi-region pain during adolescence is associated with a higher symptom burden and lower quality of life. The purpose of this study was to describe and compare the biopsychosocial attributes of single-region and multi-region pain among healthy young adolescents. Materials and Methods: We analyzed data from 10, 320 children aged 10.6 to 14 years who self-reported pain in the Adolescent Brain and Cognitive Development Study. Pain was coded as single-region or multi-region based on body map data. Results: One in 5 young adolescents indicated recent multi-region pain. Sequential regression supported improved model fit when psychological and sociocultural factors were added to a biological model of pain; however, these models improved the classification of multi-region but not single-region pain. A significant interaction effect of sex and puberty remained constant across models with increased odds of pain at each advancing pubertal stage for both sexes compared with prepuberty, but no difference between girls and boys at late puberty (adjusted odds ratio [OR]=2.45 [1.72, 3.49] and adjusted OR=1.63 [1.20, 2.23], respectively). Psychological factors improved the classification of multi-region pain with significant effects of anxiety, somatic symptoms, and somnolence. Finally, compared with White and non-Hispanic children, Black and Hispanic children were less likely to report pain (adjusted OR=0.70 [0.61, 0.80]; adjusted OR=0.88 [0.78, 0.99], respectively) but had significantly higher pain interference when pain was present (adjusted OR=1.49 [1.29, 1.73] and adjusted OR=1.20 [1.06, 1.35], respectively). Discussion: Pain is a biopsychosocial phenomenon, but psychological and sociocultural features may be more relevant for multi-region compared with single-region pain during early adolescence.